The Implementation of Business Judgment Rule Principle in Managing the Company - Busyra Azheri; Upita Anggunsuri (Nagari Law Review, 2020)
A business decision is very important to determine the quality of the Board of Directors in carrying out their duties professionally and responsibly as expected by Good Corporate Governance (GCG). The effectiveness of the Board of Directors is the center of the implementation of Good Corporate Governance. Bank Business is very risky (such: credit risk, reputation risk, etc.). The Board of Directors in making a business decision, will always face unpredictable condition. In Banking practice, the Head of Branch Office Bank is the extension of Director, if the Head of Branch Office Bank signs credit agreement out of the rules (plafond). His action has categorized as ultra vires, so the consequence is the Head of Branch Office Bank can be held responsible for his action. In this case, the Board of Directors has not taken responsibility for the action of the Head of Branch Bank, based on Business Judgment Principle, the Director has not taken its responsibility for ultra vires act which is done by the Head of Branch Office Bank, as along as Director has managed the Company in good faith, carefully and does not against the law. Therefore, Business Judgment Principle gives legal protection to the Director in making a business decision